Evaluation Of Management And Storage Of Hepatitis B And Measles Vaccines In Children At Tigarunggu Community Health Center In 2024 - Memo Apriady Tarigan; Arsiaty Sumule; Wilson Samosir; Hekdin Marsius Sipayung (Riviera Publishing, 2024)
Management vaccine is one of aspect crucial in ensure the success of the immunization program, especially For Hepatitis B and Measles vaccines which have role significant in prevent disease serious in children. However , it is still there is various constraint in management storage and distribution vaccines at the level health center that can influence quality vaccine. Research This done For evaluate management and storage Hepatitis B and Measles vaccines at the Community Health Center Tigarunggu in 2024. Study This use method observational with approach descriptive. Qualitative data obtained through interviews and observations, while quantitative data collected from indicator management vaccine like percentage vaccine damaged, percentage vaccine expired, and percentage conformity temperature storage. Population study covers all over activity management vaccines at the health center Tigarunggu, with selected samples? in a way purposive For covers aspect storage and distribution vaccine. Research result show that management storage vaccines at the Health Center Three-story building is at in category Good with percentage conformity 84.21%. System distribution vaccines also show level compliance by 94.73% against the applicable guidelines, although there is constraint in planning need vaccines and implementation procedure certain. Factors that influence management vaccine covering availability facility adequate storage, training? power health, and consistent temperature monitoring systems. Study This conclude that management vaccines at the health center Three-story building in a way general has in accordance with guidelines national, although there are areas that require repair more continue, such as planning request vaccines and treatment vaccine expired. Implications study This is the need improvement capacity source Power man through training periodic and strengthening monitoring system for ensure quality vaccine still awake.